Exploratory Study of Dimensions of Health-related Quality of Life in the General Population of South Korea - Seon-Ha Kim; Min-Woo Jo; Minsu Ock; Sang-il Lee (Korean Society for Preventive Medicine, 2017)
Objectives This study aimed to explore dimensions in addition to the 5 dimensions of the 5-level EQ-5D version (EQ-5D-5L) that could satisfactorily explain variation in health-related quality of life (HRQoL) in the general population of South Korea. Methods Domains related to HRQoL were searched through a review of existing HRQoL instruments. Among the 28 potential dimensions, the 5 dimensions of the EQ-5D-5L and 7 additional dimensions (vision, hearing, communication, cognitive function, social relationships, vitality, and sleep) were included. A representative sample of 600 subjects was selected for the survey, which was administered through face-to-face interviews. Subjects were asked to report problems in 12 health dimensions at 5 levels, as well as their self-rated health status using the EuroQol visual analogue scale (EQ-VAS) and a 5-point Likert scale. Among subjects who reported no problems for any of the parameters in the EQ-5D-5L, we analyzed the frequencies of problems in the additional dimensions. A linear regression model with the EQ-VAS as the dependent variable was performed to identify additional significant dimensions. Results Among respondents who reported full health on the EQ-5D-5L (n=365), 32% reported a problem for at least 1 additional dimension, and 14% reported worse than moderate self-rated health. Regression analysis revealed a R2 of 0.228 for the original EQ-5D-5L dimensions, 0.200 for the new dimensions, and 0.263 for the 12 dimensions together. Among the added dimensions, vitality and sleep were significantly associated with EQ-VAS scores. Conclusions This study identified significant dimensions for assessing self-rated health among members of the general public, in addition to the 5 dimensions of the EQ-5D-5L. These dimensions could be considered for inclusion in a new preference-based instrument or for developing a country-specific HRQoL instrument.